Biomass Homogeneity Reinforced Carbon Aerogels Derived Functional Phase‐Change Materials for Solar–Thermal Energy Conversion and Storage. Issue 1 (16th May 2022) - Zhang, Qingfeng; Xia, Tingfeng; Zhang, Qihan; Zhu, Yucao; Zhang, Huanzhi; Xu, Fen; Sun, Lixian; Wang, Xiaodong; Xia, Yongpeng; Lin, Xiangcheng; Peng, Hongliang; Huang, Pengru; et al.
Abstract : We devised a functional form stable composite phase‐change materials (PCMs) to achieve a three‐dimensional (3D) interconnected porous carbon aerogel structure for encapsulating polyethylene glycol (PEG). A novel homogeneity reinforced carbon aerogel with a well‐interconnected porous structure was constructed by combining a flexible carbon resource from biomass guar gum with hard‐brittle carbon from polyimide, to overcome severe shrinkage and poor mechanical performance of traditional carbon aerogel. The supporting carbon aerogel‐encapsulated PEG produced the novel composite PCMs with good structure stability and comprehensive energy storage performance. The results showed that the composite PCMs displayed a well‐defined 3D interconnected structure, and their energy storage capacities were 171.5 and 169.5 J/g, which changed only slightly after 100 thermal cycles, and the composites could maintain the equilibrium temperature at 50.0−58.1 °C for about 760.3 s. The thermal conductivity of the composites could reach 0.62 W m −1 K −1, which effectively enhanced the thermal response rate. And the composite PCMs exhibited good leakage‐proof performance and excellent light–thermal conversion. The compressive strength of the composite PCMs can improve up to 1.602 MPa. Results indicate that this strategy can be efficiently used to develop novel composite PCMs with improved comprehensive thermal performance and high light–thermal conversion. Abstract : A novel homogeneity reinforced carbon aerogel with a well‐interconnected porous structure was constructed by combining an elastic and tough carbon resource and was further applied to encapsulate polyethylene glycol fabricating a novel composite PCMs with good structure stability and phase‐change properties.